ANALISIS TINGKAT KETIDAKRATAAN JALAN NASIONAL DENGAN MENGGUNAKAN ALAT NAASRA - Anggita Yuliani; Samsul Bahri; Yuzuar Afrizal (Inersia: Jurnal Teknik Sipil, 2019)
The level of unevenness of the road is a parameter that is often used to measure the roughness of a road segment. The tools and methods used are named NAASRA. The NAASRA tool produces IRI values which then used to classifiedwith road condition according to Binamarga 2005. The purpose of this research is to test the value of road unevenness (IRI), to test the level of road stability, and to arrange the handling needs on Betungan-Padang Serai road. The results show that the Betungan-Padang Serai roads have good roads along 4150 m (75%), medium conditions along 400m (7%), minor damage conditions along 500m (9%), and severe damage conditions of 500 m (9%). The result of road stability test shows that steady road condition is 4550 m (82%) and unsteady road is 1000 m (18%). Routine maintenance is required for 4150 m (75%), major and minor rehabilitation of 400 m (7%), and 1000 m (18%) reconstruction.